Feasibility Study of Snail Farming in Indonesia - Haryono, Haryono (West Science Social and Humanities Studies, 2024)
This study evaluates the economic feasibility of snail cultivation in Indonesia by analyzing the impact of market demand, cultivation technology, and environmental conditions. A quantitative approach was employed, surveying 150 respondents using a Likert scale (1-5), with data analyzed via SPSS version 26. The results reveal that market demand is the most significant factor influencing economic feasibility, followed by cultivation technology and environmental conditions. All three variables positively and significantly affect the viability of snail farming. These findings suggest that increasing market demand, adopting modern farming technologies, and maintaining favorable environmental conditions are essential for promoting snail cultivation in Indonesia. This study provides valuable insights for policymakers, investors, and farmers interested in developing snail farming as a sustainable agricultural business.